Malawi : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2005)
This report on the Observance of Standards and Codes data module provides a review of Malawi's data dissemination practices against the IMF's General Data Dissemination System (GDDS), complemented by the in-depth assessment of the quality of five macroeconomic datasets. With the exception of the fiscal sector, Malawi publishes statistics for most of the comprehensive frameworks, data categories, and indicators recommended in the GDDS. The legal and institutional framework for the production of the five macroeconomic datasets of all institutions responsible for collecting, processing, and disseminating macroeconomic statistics is broadly adequate.